PARTISIPASI MASYARAKAT DALAM PENGELOLAAN SAMPAH DI KECAMATAN GENUK KOTA SEMARANG (Analisis Perda Nomor 6 Tahun 2012 Tentang Pengelolaan Sampah) - Driyantama, Bagas Putra; -, Turtiantoro - (Journal of Politic and Government Studies, 2020)
Daily waste in the city of Semarang currently reaches 1270 tons every day. Meanwhile, the amount of waste managed at TPA Jatibarang in the 2017-2018 period reached 850 tons every day. This is the concern of the Semarang City Government so that the amount of waste can be reduced. In addition, the urbanization of neighboring regencies and cities has also caused Semarang City to produce large amounts of waste. There are two problem formulations in this research, namely (1) How is community participation in waste management in Genuk District? And (2) What influences community participation in waste management in Genuk District? Meanwhile, the purpose of this study is to determine community participation in waste management in Genuk District and to identify what influences community participation in waste management in Genuk District. This descriptive qualitative research was employed. Data were collected use interview, questionnaire, observation, and documentation. Based on the results of this study, there are two research findings, (1) public awareness of not littering. Community habits like this make the environment worse, because it makes sewers stagnate, like sewer water becomes dirty and creates a bad smell. (2) not all people know the technique of sorting waste between organic and non-organic. Organic and nonorganic waste must be separated because of the different processing processes. From the results of this study, it can be concluded that the Self-Help Groups and waste banks in Genuk District have played an active role in waste management, for example reducing waste and sorting from waste sources. Community participation in waste management is quite good, especially at the stage of disposing of waste from household waste management by establishing a waste bank in the context of reducing waste to TPS and utilizing waste recycling to make it a high economic value.